2017
DOI: 10.1002/capr.12138
|View full text |Cite
|
Sign up to set email alerts
|

Are rupture–repair episodes related to outcome in the treatment of trauma‐exposed World Trade Center responders?

Abstract: Objective This study aimed to examine rupture–repair (R–R) episodes in a sample of adult World Trade Center responders (N = 32) who engaged in integrative psychotherapy for the treatment of posttraumatic stress disorder (PTSD) in an outpatient clinic. Method Participants rated therapeutic alliance after each session, and presence of R–R episodes was calculated throughout the course of treatment. We predicted that patients who experienced R–R episodes would have significantly better treatment outcomes than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In addition to looking at the relationship between alliance ratings and outcome, several studies looked at the effect of changes in alliance, known as ruptures (i.e., significant decreases in therapeutic alliance) and repairs (i.e., subsequent increases in alliance), on therapy outcome. One such study utilized the aforementioned sample of 9/11 responders and examined the role of rupture‐repair episodes (i.e., a decrease of one standard deviation in the CASF‐P between sessions, followed by an increase of at least one standard deviation in the score at any point before the end of treatment) on general psychiatric outcome (Haugen, Werth, Foster, & Owen, 2017). Although nearly 38% of their participants ( n = 12) experienced a rupture‐repair episode as defined, there was no significant difference in symptom change across treatment for these participants those who did not experience rupture repair, except for a moderate but non‐significant association with the “Goals/Task” subscale.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to looking at the relationship between alliance ratings and outcome, several studies looked at the effect of changes in alliance, known as ruptures (i.e., significant decreases in therapeutic alliance) and repairs (i.e., subsequent increases in alliance), on therapy outcome. One such study utilized the aforementioned sample of 9/11 responders and examined the role of rupture‐repair episodes (i.e., a decrease of one standard deviation in the CASF‐P between sessions, followed by an increase of at least one standard deviation in the score at any point before the end of treatment) on general psychiatric outcome (Haugen, Werth, Foster, & Owen, 2017). Although nearly 38% of their participants ( n = 12) experienced a rupture‐repair episode as defined, there was no significant difference in symptom change across treatment for these participants those who did not experience rupture repair, except for a moderate but non‐significant association with the “Goals/Task” subscale.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the remaining four studies that failed to find an association between alliance and outcome used uncommon measures of alliance (Brady et al, 2015;Haugen et al, 2016Haugen et al, , 2017. Such measures may not fully capture the same construct as more commonly used measures of alliance, particularly as a relationship between alliance and treatment outcome was found in so many other studies of a similar population using more common measures (e.g., Forbes et al, 2008;McLaughlin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the resolution process of ruptures can harness the therapeutic potential of interaction between patient and therapist. There is growing evidence that patient and therapist dyads with unrepaired alliance ruptures have poor treatment outcomes, and those with repaired ruptures have enhanced outcomes (Haugen et al, 2017, see also Zilcha-Mano et al, 2019).…”
Section: Jessica: Exactlymentioning
confidence: 99%
“…Exploring relationship ruptures may provide the client with an opportunity for corrective learning about themselves and others. Haugen, Werth, Foster, and Owen (2017) studied different rupture patterns in psychotherapy longitudinally, differentiating between ruptures without repair (10.7%), ruptures with repair (14.7%), and no-rupture patterns (74.5%). They found that the ruptures without repair were associated with inferior treatment outcomes.…”
Section: Addressing Relationship Rupturesmentioning
confidence: 99%